Keefektifan Teknik Modeling Dalam Meningkatkan Tanggung Jawab Siswa Kelas VIII A - Ahsan Ama; Hamizan Rabban (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2023)
With increasingly advanced technological developments, some of these problems can be minimized with the latest technology in the construction sector known as Building Information Modeling (BIM). With BIM, all parties involved in the project (stakeholders) can collaborate from the planning stage before the project is carried out, thereby reducing the potential for errors in development implementation (Mafrul, 2022). The use of BIM can provide the various functions necessary to model the entire life cycle of a building, while also providing a basis for dealing with changes and construction progress in positions and correlations between project teams. Proper implementation of BIM enables increasingly integrated design and construction processes, creating buildings with better quality, more efficient production costs, and shorter project completion times (Khairi et al., 2022b).